The Urgency of Actors' Presence on Trending Hashtags on Twitter's New Media in the Frame of Social Network Analysis - Indah Permata, Ida Ayu Shinta; Gora, Radita (Journal La Bisecoman, 2024)
The phenomenon of using social media as a new media to meet the needs of information in the community is the result of the rapid development of the internet. Now the needs of the community are easily met, because various things have been contained in it. This can be analyzed based on the phenomenon of trending topics through hashtags on social media twitter using Social Network Analysis (SNA). The purpose of writing this research article is that with so many soap operas in Indonesia that last more than one year on the Indonesian screen, it becomes an interesting thing, but it is not only in the real world, but has become a conversation in cyberspace, Twitter in particular. Using mixed method research methods with actor and network analysis techniques in the quantitative and technical domains of observation, record and descriptive analysis techniques, with Bruno Latour's network study approach. The subjects of the study were the network of actors and the flow of information on the hashtag #IkatanCintaEp1012. The use of Twitter social media as a new media can show networks and actors that make the spread of information and connectivity between fans in the virtual world increasingly stronger and faster in a hashtag network.